Role Modeling Based on the Qur'an and Hadith as a Preventive Strategy Against Bullying in Contextual Islamic - Iffatut Tazkiyyah; Faqih Abdul Aziz; Ali Mas'ud; Ali Mudlofir; Asep Saepul Hamdani (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2026)
Bullying in Islamic school environments has become a serious problem reflecting a profound gap between students' religious knowledge and their social behavior. This study aims to construct a role modelling model based on the Qur'an and Hadith as a preventive strategy against bullying within contextual Islamic Religious Education (PAI) learning. The study employed a qualitative approach through library research, utilizing content analysis, comparative analysis, and conceptual synthesis of relevant primary and secondary sources. The findings reveal two major points: first, a theoretical construction of Islamic role modelling is established through an integrative synthesis between the concept of uswah hasanah in the Qur'an and Hadith and Bandura's Social Learning Theory, producing the ITTIBA' conceptual model (tafakkur, tadabbur, ta'wid, niyyah); second, its implementation operates on three levels personal teacher exemplarity, narrative exemplarity through Prophetic biography, and school community exemplarity operationalized through four stages of contextual learning. The study concludes that the moral knowledge-behavior gap underlying bullying in Islamic schools can only be bridged through three simultaneous mechanisms: affective bridging, identity integration, and ecological support, all of which require the presence of authentic and consistent PAI teachers as living role models. Keywords: Role modelling; Qur'an and Hadith; bullying; contextual Islamic education; Islamic character education